Perceived leadership quality and empathy among Indian undergraduate medical students - Himel Mondal; Sachin Soni; Manas Ranjan Sahoo; Shaikat Mondal; Koushik Saha; Biswajit Maharana; Bhagyajyoti Priyadarshini; Joshil Kumar Behera (Wolters Kluwer Medknow Publications, 2023)
BACKGROUND: Efficient leaders from the medical fraternity may understand healthcare in depth. Empathy is important for patient care, job satisfaction, and the psychological well-being of doctors. Empathic leadership is concerned with an interest in the people around them. This study aimed to observe the perceived leadership quality and empathy among Indian medical undergraduate students, find any correlation between them, and assess age, sex, and semester of study as predictor variables for leadership and empathy.MATERIALS AND METHODS: An online cross-sectional survey was conducted on Google Forms with undergraduate medical students in India with a convenient snowball sample. The Abbreviated Self Leadership Quality (ASQL) was used to find the leadership quality and the eight-item Empathy Quotient (EQ-8) to find the empathy. Spearman's correlation coefficient was calculated between ASQL and EQ-8 score. Age, sex, and semester were used as predictor variables in regression analysis with leadership and empathy as dependent variables.RESULT: A total of 439 (50.8% male, 49.2% female) Indian undergraduate students participated in the study. Males showed higher leadership qualities. There was no gender difference in empathy. Leadership was positively correlated (rs =0.13, P = .006) with empathy in the overall sample. The age (P = .001), sex (P < .0001), and semester of study (P < .0001) successfully predicts leadership (F = 57.167, P < .0001). Although age, sex, and semester combined successfully predict empathy (F = 5.31, P = .001), individually, only a semester of study (P = .009) significantly contributes to the prediction.CONCLUSION: Male and female medical students show a similar level of empathy but male shows higher leadership quality. Leadership and empathy are positively correlated; hence, students with higher leadership quality would show higher empathy and vice versa. The age, sex, and semester of study are determinants of leadership whereas semester of study is the determinant of empathy.